Beyond initial impacts: The evolving COVID-19 context and food system resilience - McDermott, John; Lee, Deborah; McNamara, Brian; Swinnen, Johan (International Food Policy Research Institute, 2022)
As we mark the second anniversary of the start of the COVID-19 pandemic, the health, economic, and social disruptions associated with this global crisis continue to evolve. The impacts of the pandemic are prolonged and likely to endure for years to come. Poor, marginalized, and vulnerable groups have been disproportionately affected, with informal and migrant workers, refugees and displaced persons, and women and children particularly vulnerable and adversely impacted.